Urban-Rural Differences in Food Beliefs and Practices in Indonesia: A Qualitative Study - Annisa Utami Seminar; Vieta Annisa Nurhidayati; Ali Khomsan; Hadi Riyadi; Anna Vipta Resti Mauludyani; Anna Fatchiya; Bernatal Saragih; Abdul Rahim; Made Darawati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Food beliefs and cultural practices have a significant influence on food choices, recommendations, and taboos, with variations shaped by the context of ecological, social, and local knowledge. Rural populations generally adhere to long-established traditional practices, whereas urban environments undergo more rapid dietary transitions driven by globalization and the commercial food industry. This cultural framework shapes individual interpretations of nutritional information, often leading to the rejection of health messages that contradict established belief systems. In Indonesia, considerable ethnic and geographical diversity gives rise to culturally embedded diets that can impact nutritional status; however, the dynamic interactions between food choices, recommendations, and taboos remain insufficiently studied. To address this gap, a qualitative study that explores regional variations in food beliefs and practices in Indonesia, focusing on urban–rural differences across diverse socio-ecological settings was conducted. Methods: In-depth interviews with 28 respondents and focus group discussions with 42 respondents were conducted in four provinces (West Java, Central Sulawesi, East Kalimantan, and West Nusa Tenggara) under the Socio-ecological Model (SEM) framework to investigate how dietary choices, food recommendations, and food taboos are shaped. The study was conducted in 2022. Ethical approval was obtained and all participants provided consent. Results: The findings reveal three main insights: (1) a paradoxical decoupling between dietary diversity and nutritional outcomes, wherein greater dietary diversity in Eastern Indonesia does not directly correlate with better nutrition outcomes; (2) food recommendations for mothers and infants vary, with urban areas favoring commercial products and rural areas relying more on local knowledge; and (3) food taboos persist across regions, particularly in rural Eastern Indonesia, often affecting infant and maternal nutrition. Conclusion: This study contributes to a nuanced, culture-sensitive framework to inform health communication and nutrition policies in Indonesia. These findings highlight the need for culturally sensitive and context specific nutrition policies.